Fowl cholera vaccine production: screening and optimization of media in shake flask culture - Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Yob, Nor Jannah; Samsury, Intan Zahrah; Syed Hassan, Sharifah; Ngah Hamid, Akma (IIUM Press, 2011)

(untitled)
The screening and optimization for fowl cholera vaccine production were carried out in shakes flask experiments with composition 10% of inoculums and 90% of media. The experiments were designed and analyzed using Statsoft software "STATISTICA Version 6.0". Initially seven variables were screened using Placket Burman Design. The result of screening in shake flasks indicated that glucose, sodmm hydrogen carbonate and sodium chloride were the main variables that affected the P. multocida fermentation. These three variables were then optimized and analyzed by using Box Behnken design. The optimization and critical values of glucose, sodium hydrogen carbonate and sodium chloride were obtained which correspond to 2.651g, 5.052 g, and 5.437 g, respectively. The correlation between these three variables on protein concentration and total cell number were investigated using Response Surface Methodology. These critical concentrations of the glucose, sodium hydrogen carbonate and sodium chloride were transferred to second part of the project for scale-up fermentation in 2 liter laboratory scale fermenter.